Citizen science engagement: Insights from the ’Bridging Worlds’ initiative on libraries as connectors - Nurfarawahidah B.; Hamzah , Mohd Faizal; Che Jaafar , Cik Ramlah; Shunmugam, Ranita Hisham; Zilah , Amirul Firdaus (Journal of Islamic, Social, Economics and Development, 2024)
Recently, citizen science has been an active way to mobilize the public in conducting scientific research to put more focus on community groups by improving their involvement in the research process and level of scientific literacy. Libraries and non-governmental organizations (NGOs) have served as the main users and supporters of such events. The assignment reviews the evaluation of the "Bridging Worlds: Libraries as Connectors in Citizen Science" event conducted by the Librarians Association of Malaysia in cooperation with academic libraries to promote citizen science. The purpose of the program was to educate the target audience on the notion of citizen science and evaluate whether the participants would grasp the extent of the roles that PPM and libraries play in the identified context. The designated research used a quantitative design in which 188 participants were asked to take a test before and after the program. The latter showed an increase in learners' awareness of the concept of citizen science and willingness to engage actively in the identified type of activity. This article shows that the role of the NGOs, for example, PPM, and academic libraries in the process of promoting the citizen science movement and involving the public was seen as critically significant. The example of collaboration shows that cooperation between NGOs, libraries, and local communities can support the evolution of long-term citizen science. The featured activity plays an important role. It might also be better if future programs focus on revealing the real results of the citizen science experience. Moreover, the study proposes to combine a monitoring and feedback system, which would allow monitoring the dynamics of the participants' success. Thus, the findings present important lessons and recommendations for the formulation and adaptation of citizen science policies and practices in Malaysia. It was mainly identified that cooperation between NGOs, libraries, and communities should continue to be fostered.